Prevalence of cancer related to sociodemographic characteristics and prevention strategies in Mogadishu, Somalia - Warsame, Abdullahi Abdulkarim; Sönmez, Recep Erçin; Muse, Mohamed Moalim; Guled, Ahmed Yusuf; Alimoğlu, Orhan (Bangladesh Journal of Medical Science, 2021)
Background: Cancer is the second leading cause of death globally and is estimated to account for 9.6 million death in 2018. Lung, prostate, colorectal, stomach and liver cancers are those most common among men; while breast, colorectal, lung, cervix and thyroid cancers are most frequent types among women. Objectives: The present study aims to assume a leading role for forthcoming researches to establish a national cancer registry database in Mogadishu, Somalia. Methodology: This is a retrospective 6-months analysis of cancer patients whose data were achieved from pathology department registries of Liban and Veritas Hospitals in Mogadishu, Somalia. Results: 126 (M/F: 51 (41.5%) / 75 (59.5%)) patients were included in the study. Esophagus had been recorded as the most frequent site of organ which was diagnosed with cancer (n=74 (58.7%)). Squamous cell carcinoma was recorded to be the most frequent histopathologically confirmed subtype (n=91 (72%), M/F:34/57), which was followed by adenocarcinoma (n=16 (12.7%), M/F:11/5) and sarcoma (n=6 (4.8%), M/F:5/1) consequtively. Majority of both squamous cell carcinoma (n=37 (40.7%)) and sarcoma patients (n=3 (50%)) were >60 years of age, whereas patients diagnosed with adenocarcinoma (n=7 (43.75%)) were between 41-50 years of age. Conclusion: Emphasis should be placed on finding ways to ensure early detection and diagnosis of cancer in Mogadishu, Somalia promptly. That should begin by giving educations to community to raise public awareness, and establishing national cancer registry to reveal up-to date data in order to make risk assessment and coordinate management strategies accordingly. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.756-761